2021
DOI: 10.3390/ijms22126385
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Drug Resistance in Glioblastoma

Abstract: Glioblastoma multiforme (GBM) is the most common and fatal primary brain tumor, is highly resistant to conventional radiation and chemotherapy, and is not amenable to effective surgical resection. The present review summarizes recent advances in our understanding of the molecular mechanisms of therapeutic resistance of GBM to already known drugs, the molecular characteristics of glioblastoma cells, and the barriers in the brain that underlie drug resistance. We also discuss the progress that has been made in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 128 publications
(139 reference statements)
0
39
0
Order By: Relevance
“…The predominant effect of ionizing radiation (IR) and DNA-targeted chemotherapy on cancer cells is the induction of DNA damage of which DNA double-strand breaks are most severe, ultimately leading to cell cycle arrest, cell death, and abrogation of clonogenic survival [ 23 ]. Accordingly, resistance against DNA damage-induced cell death and clonogenic inactivation is a major obstacle in current GBM treatment [ 24 ], and frequently derives from alterations both in abundance and functionality of DNA damage response (DDR) regulators [ 25 ]. In the present study, we examined the basal mRNA expression levels of 38 DDR genes in a panel of seven human GBM cell lines in comparison to primary human astrocytes and observed a thorough and massive upregulation of multiple DDR genes analyzed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The predominant effect of ionizing radiation (IR) and DNA-targeted chemotherapy on cancer cells is the induction of DNA damage of which DNA double-strand breaks are most severe, ultimately leading to cell cycle arrest, cell death, and abrogation of clonogenic survival [ 23 ]. Accordingly, resistance against DNA damage-induced cell death and clonogenic inactivation is a major obstacle in current GBM treatment [ 24 ], and frequently derives from alterations both in abundance and functionality of DNA damage response (DDR) regulators [ 25 ]. In the present study, we examined the basal mRNA expression levels of 38 DDR genes in a panel of seven human GBM cell lines in comparison to primary human astrocytes and observed a thorough and massive upregulation of multiple DDR genes analyzed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The authors demonstrated that TMZ (at therapeutic concentration) increased the transport of Pgp substrates across human brain microvascular endothelial cells and decreased the expression of Pgp. The scenario is much more complex for the blood-brain tumor barrier (BBTB), which reflects the complex regional heterogeneity of immune cell populations compared to the BBB [33]. The BBTB is generally considered 'leakier' than the BBB, which is characterized by aberrant pericyte distribution and loss of astrocytic endfeet and neuronal connections [34,35].…”
Section: Landscapes Of Unique Immune Suppression In Glioblastomamentioning
confidence: 99%
“…The scenario is much more complex for the blood-brain tumor barrier (BBTB), which reflects the complex regional heterogeneity of immune cell populations compared to the BBB [33]. The BBTB is generally considered 'leakier' than the BBB, which is characterized by aberrant pericyte distribution and loss of astrocytic endfeet and neuronal connections [34,35].…”
Section: Landscapes Of Unique Immune Suppression In Glioblastomamentioning
confidence: 99%
“…These properties could lead to the formation of a heterogeneous landscape not only by malignant cells that differ from each other, depending on their metabolic requirements, but also by the presence of endothelial cells and populations of the innate and adaptive immune system [6,7]. Tumor heterogeneity shaped by genetic and metabolic aberrations as well as by immunoediting mechanisms confers GBM high resistance to drugs, which leads to poor prognosis for the patient [8]. Therefore, the interconnections between two or more malignant cell hallmarks and the revelation of intercellular associations could offer novel insights into cancer biology, as well as promising targets for therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%